The brazilian teenagers and the reasons why they don't use condom to prevent HIV/Aids - Abner Florêncio da Silva, Gilberto de Lima Guimarães (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v4i1.3311